Socio-economic factors as predictors of self-medication among automobile technicians in Ibadan North Local Government Area of Oyo State, Nigeria (2014)
The study examined socio-economic factors as predictors of self-medication among automobile technicians in Ibadan North Local Government Area of Oyo State, Nigeria. Descriptive survey research design was employed in the study. A sample of 123 respondents was selected using simple random sampling technique. Two research hypotheses were tested. Self developed .validated questionnaire with reliability co-efficient of 0.65 was used to collect data. Data were analysed with the use of percentage and inferential statistics of multiple regression at 0.05 level of significance. The result showed that, joint effect of socio-economic variables (poverty, ignorance of negative effect of self medication and weak government hospital health care service) on self mediation was significant (F(3.118) = 13.755; R =0.509; R2 =0.259; Adj. R2 =0.240; P<05). Self medication constitutes public health problem Therefore health education, effective poverty alleviation programme, public drug education and thorough supervision of government health facilities were finally recommended